2011
DOI: 10.1212/wnl.0b013e318232ab65
|View full text |Cite
|
Sign up to set email alerts
|

OnabotulinumtoxinA improves quality of life and reduces impact of chronic migraine

Abstract: This study provides Class 1A evidence that onabotulinumtoxinA treatment reduces headache impact and improves HRQoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
101
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(111 citation statements)
references
References 35 publications
5
101
1
3
Order By: Relevance
“…This study may further support the role of a peripheral mechanism in the complex migraine cascade. Botulinum toxin-A (Botox) injections have been recognized and Food and Drug Administration-approved as an effective temporary preventative therapy for chronic migraine headaches, [15][16][17] and surgical decompression or neurectomy of select injection sites has been used to achieve long-term improvement of patients with diagnosed peripheral nerve compression. [6][7][8][9][10][11][12][13] …”
mentioning
confidence: 99%
“…This study may further support the role of a peripheral mechanism in the complex migraine cascade. Botulinum toxin-A (Botox) injections have been recognized and Food and Drug Administration-approved as an effective temporary preventative therapy for chronic migraine headaches, [15][16][17] and surgical decompression or neurectomy of select injection sites has been used to achieve long-term improvement of patients with diagnosed peripheral nerve compression. [6][7][8][9][10][11][12][13] …”
mentioning
confidence: 99%
“…Nearly 4 million people have had onobotulinum toxin A injections for headache. Onobotulinum toxin A has been found to significantly improve quality of life and reduce headache impact [7].…”
Section: First-line Preventive Medications For Migrainementioning
confidence: 99%
“…They also demonstrated significant reductions in several other measures of migraine symptomology such as cumulative hours of headaches, headache days, and days of moderate/severe headaches [9]. Further studies indicated efficacy in reducing disease burden based on patient quality of life questionnaires [10,11]. However, studies evaluating the effect of BTX-A on episodic migraines so far have not shown significant benefits [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Over time, a number of well-designed large-scale studies demonstrated that this neurotoxin to be effective in reducing several measures of migraine symptomology [5][6][7][8][9][10][11]. The first major landmark study, called the PREEMPT (Phase III Research Evaluating Migraine Prophylaxis Therapy) trials, indicated that BTX-A is indeed effective and safe in treating migraine headaches.…”
Section: Introductionmentioning
confidence: 99%